Exploring Types of Language Functions in Mufasa from The Lion King Movie - Ni Made Nadia Widyasari; Sulatra , I Komang (Universitas Islam Negeri Palopo, 2025)
This study examines the language functions used by Mufasa in Mufasa: The Lion King and the contexts in which they appear. Previous research has applied Jakobson’s model to film dialogue, but most focus on adult or action-based characters, leaving little attention to symbolic figures in animated films. This study addresses that gap by analyzing Mufasa, a character whose speech reflects leadership, morality, and emotional guidance. Using a descriptive qualitative approach, 120 utterances from the film’s official script were collected, coded, and categorized according to Jakobson’s six functions: referential, emotive, conative, phatic, metalingual, and poetic. Contextual details such as tone, setting, and conversational partner were also considered to ensure accuracy. The results show that Mufasa’s speech is dominated by the referential, emotive, and conative functions (24 utterances each, 20%), followed by metalingual and poetic (18 utterances each, 15%), and phatic (12 utterances, 10%). Referential utterances conveyed facts and knowledge, emotive ones expressed love or concern, and conative statements directed Simba’s actions. Metalingual and poetic functions added clarification and symbolic imagery, while phatic expressions maintained social bonds. These findings demonstrate that Mufasa’s language is intentional and multifaceted, reinforcing his role as father, mentor, and king while showing how animated films use language to convey values and relationships.